STUDI TENTENG BUSANA PENGANTIN TRADISIONAL DI KABUPATEN MUKOMUKO PROVINSI BENGKULU - Misnawati, Tri; Adriani, Adriani; Nelmira, Weni (Journal of Home Economics and Tourism, 2017)
Betabur shirt is a traditional wedding dress used during wedding ceremony in Mukomuko Regency of Bengkulu Province. Characteristic of this traditional wedding dress on the head decoration using a headlight on the groom, singal on the bride and use the birds kilek. The research method used is descriptive qualitative method. Data were collected using observation, interview and documentation techniques. Types of data in the form of writing and non-writing (recording) obtained through interviews, documentation and literature study. Data are reviewed and analyzed by data reduction steps, data presentation and conclusions. The validity of the data by extending the observation, increasing perseverance, triangulation, peer and auditing. The results showed that the design of traditional women's wedding dress Mukomuko consists of the clothes betabur,4songket cloth, accessories and accessories. The groom is comprised of baju betabur, pants, songket cloth, accessories and accessories. How to wear traditional women's wedding dress starting from the bun, head ornament (singal), songket cloth, shirt, pedalan, shoulder shavings, necklaces, bird kiln, earrings, bracelets and sandals. The groom begins with pants, songket cloth, baju betabur, peding, necklaces, and sandals. The traditional bridal attire of men and women has meaning, symbol or advice on the symbols used.Keywords: design (model, material, color and decoration), complementary clothing, manner of usage and meaning.